Chemical components of respirable particulate matter associated with emergency hospital admissions for type 2 diabetes mellitus in Hong Kong. (December 2016) - Sun, Shengzhi; Qiu, Hong; Ho, Kin-Fai; Tian, Linwei
Abstract: Background: Epidemiological studies have shown that short-term exposure to particulate matter (PM) mass is associated with diabetes morbidity and mortality, although inconsistencies still exist. Variation of chemical components in PM may have contributed to these inconsistencies. We hypothesize that certain components of respirable particulate matter (PM10 ), not simply PM10 mass, can exacerbate symptoms or cause acute complications for type 2 diabetes mellitus (T2DM). Methods: We used a Poisson time-series model to examine the association between 17 chemical components of PM10 and daily emergency hospital admissions for T2DM among residents aged 65 years or above from January 1998 to December 2007 in Hong Kong. We estimated excess risk (ER%) for T2DM hospitalizations per interquartile range (IQR) increment in chemical component concentrations of days at lag0 through lag3, and the moving average of the same-day and previous-day (lag0–1 ) in single-pollutant models. To further evaluate the independent effects of chemical components on T2DM, we controlled for PM10 mass, major PM10 chemical components, and gaseous pollutants in two-pollutant models. Results: In the single-pollutant models, PM10 components associated with T2DM admissions include: elemental carbon, organic carbon, nitrate, and nickel. The ER% estimates per IQR increment at lag0–1 for these four components were 3.79% (1.63, 5.95), 3.74% (0.83, 6.64), 4.58% (2.17, 6.99), and 1.91% (0.43, 3.38), respectively. Risk estimates for nitrate and elemental carbon were robust to adjustment for co-pollutant concentrations. Conclusions: Short-term exposure to some PM10 chemical components such as nitrate and elemental carbon increases the risk of acute complications or exacerbation of symptoms for the T2DM patients. These findings may have potential biological and policy implications. Highlights: Few studies have investigated PM10 components on T2DM emergency hospitalization. EC and NO3 − were associated with T2DM emergency hospitalization. Traffic, marine vessels, industrial and agricultural combustion may be targeted on.